A green and efficient low-temperature SCR denitration catalyst and its preparation method
By using specific component formulas and modification treatments in low-temperature SCR denitration catalysts, an efficient low-temperature SCR denitration catalyst is formed, which solves the problems of existing catalysts with low activity, low efficiency and insufficient anti-poisoning ability in low-temperature environments, and achieves Efficient nitrogen oxide reduction reaction and good poisoning resistance.
Patent Information
- Application Number
- CN202411320339.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing SCR denitrification catalysts have low activity and low efficiency in low temperature or ultra-low temperature flue gas environments, and have weak anti-sulfur and water poisoning ability, and cannot tolerate alkali metal poisoning, resulting in low denitrification efficiency.
It adopts a formula of nano titanium dioxide, ferromanganese powder, ammonium metavanadate, chromium nitrate, ammonium niobium oxalate, germanium dioxide, molybdate, activated carbon, rare earth oxide and other components, and forms it through modified ferromanganese powder and sintering treatment. Highly efficient low-temperature SCR denitration catalyst.
In the range of 120 ~ 300 ° C, especially the range of 120 ° C ~ 150 ° C, it significantly improves the activity and denitration efficiency of catalysts, enhances sulfur anti -poisoning ability, and can resist alkaline metal poisoning. Oxide reduction reaction.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and relates to a green and efficient low-temperature SCR denitration catalyst and a preparation method thereof. Background Art
[0002] Nitrogen oxides (NO x ) is an important air pollutant that poses a serious threat to human health and has attracted widespread attention from all over the world.
[0003] To reduce NO x To prevent the harm caused by NOx, humans continue to study denitrification technology and obtain beneficial results. Existing denitrification technology is mainly divided into pretreatment technology (low NOx x Combustion technology) and post-treatment technology (flue gas denitrification technology), pre-treatment technology due to the reduction of NO x The effect is limited and the equipment conditions are limited. It is difficult to meet the emission requirements, so flue gas denitrification technology has become an important guarantee. In flue gas denitrification technology, selective catalytic reduction (SCR) has become the most efficient and widely used denitrification method, such as large-scale use in boiler flue gas of coal-fired power plants, but the V2O5 / TiO2 catalyst used by SCR can usually only be used in flue gas above 300°C. Otherwise, denitrification will cause serious sulfur dioxide poisoning and water poisoning, as well as alkali (alkaline earth) metal poisoning in flue gas conditions below 300°C, and this poisoning is irreversible. However, the flue gas temperature at the denitrification reactor of many industrial kilns is lower than 300°C, or even lower than 150°C, such as coke ovens, sintering machines, pelletizing, garbage incinerators, biomass boilers, hazardous waste incinerators, chemical furnaces, catalytic cracking furnaces, glass kilns, ceramic kilns, cement kilns, forging furnaces, casting furnaces, heat treatment furnaces, etc. The flue gas temperature is mostly 120~300°C. In order to meet the ultra-low emission requirements of nitrogen oxides, the currently commonly used method is to heat the flue gas to 300°C or above so that medium and high temperature catalysts can be used for denitrification.
[0004] Existing catalysts also generally have some problems: low activity and low efficiency in low or ultra-low temperature flue gas environments, weak resistance to sulfur and water poisoning, and not resistant to alkali (earth) metal poisoning, which affects the denitrification efficiency. Summary of the invention
[0005] In order to solve the problems of low activity, low efficiency, weak resistance to sulfur and water poisoning, and inability to alkali (earth) metal poisoning in low or ultra-low temperature flue gas environments of existing denitrification catalysts, the present invention provides a green and efficient low-temperature SCR denitrification catalyst with high activity and high denitrification efficiency in low or ultra-low temperature flue gas environments. The catalyst has strong resistance to sulfur and water poisoning, and is resistant to alkali (earth) metal poisoning, and is suitable for the range of 120~300℃, especially the range of 120℃~150℃.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A green and efficient low-temperature SCR denitration catalyst, the catalyst formula is as follows, by mass percentage, 50-55% of nano titanium dioxide, 5-10% of ferromanganese powder, 0.5-1.5% of ammonium metavanadate, 1-2% of chromium nitrate, 1.5-1.8% of ammonium niobium oxalate, 5-10% of germanium dioxide, 2-3% of molybdate, 1-3% of activated carbon, 2-5% of rare earth oxide, 1-2% of dispersant, 2-3% of binder, and 16-18% of deionized water.
[0008] Furthermore, the molybdate is one or more of ammonium molybdate, sodium molybdate, calcium molybdate, and magnesium molybdate.
[0009] Furthermore, the rare earth oxide is one or more of lanthanum oxide, cerium oxide, praseodymium oxide, yttrium oxide, europium oxide, and gadolinium oxide.
[0010] Furthermore, the dispersant is polyethylene glycol, and the number average molecular weight of the polyethylene glycol is 2000-4000.
[0011] Furthermore, the adhesive is polyethylene oxide, and the number average molecular weight of the polyethylene oxide is 2,000,000-3,000,000.
[0012] A method for preparing a green and efficient low-temperature SCR denitration catalyst. The specific process of the method for preparing a green and efficient low-temperature SCR denitration catalyst is as follows: S1: modifying ferromanganese powder. The specific method is as follows:
[0013] S1.1: grinding the ferromanganese powder in a ball mill at a speed of 400 r / min for 4 h to obtain ferromanganese powder with a particle size of 750 mesh;
[0014] S1.2: dissolve ammonium metavanadate, chromium nitrate and ammonium niobium oxalate in 10% oxalic acid solution to obtain a mixed solution with a mass fraction of 10-20%, and then add 0.5-1wt% hydrazine hydrate to obtain a mixed solution A. Then, put the ferromanganese powder obtained by grinding in S1.1 into the mixed solution A, heat it to 40°C, and perform ultrasonication for 0.5h to obtain a solid-liquid mixture B;
[0015] S1.3: Heat the solid-liquid mixture B to 60°C, stir at 60°C at a speed of 150 r / min for 4 h, cool to room temperature after the reaction is complete, and filter to obtain a mixture C;
[0016] S1.4: Dry the mixture C at 110° C. for 14 h under a nitrogen atmosphere to obtain a modified ferromanganese powder;
[0017] S2: Grind the modified ferromanganese powder, germanium dioxide and nano titanium dioxide in a ball mill according to the formula ratio. The speed of the ball mill is 300 r / min. The grinding time is 0.5 h. The ground mixture is heated from room temperature to 400° C. in a muffle furnace and sintered for 4 h. After sintering, it is cooled to room temperature to obtain a mixture D.
[0018] S3: Place mixture D, molybdate, activated carbon, and rare earth oxide in a high-speed mixer, add deionized water, and then add a dispersant and a binder to stir and mix. The speed of the mixer is 4000 r / min. The mixing time is 4-5 h to obtain a mixture E.
[0019] S3: The mixture E is extruded into a honeycomb shape by a mold, and then put into a drying room for drying. The mixture is kept warm for 24 hours at 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C and 75°C respectively, wherein the humidity in the drying room is required to be maintained above 80% before 45°C. After drying for at least 240 hours, the moisture content of the finished catalyst product drops below 20%, and then it is calcined at 550-650°C for 30-40 hours to obtain the green and efficient low-temperature SCR denitration catalyst.
[0020] Furthermore, the heating rate of the muffle furnace in S2 is 3°C / min.
[0021] Furthermore, the particle size of the mixture E in S3 is 10-15 mesh.
[0022] The catalyst prepared by the present invention can effectively promote the reduction reaction of nitrogen oxides, generate harmless nitrogen and water, and significantly reduce the concentration of nitrogen oxides in flue gas. In the preparation process of the catalyst, environmentally friendly raw materials and processes are used to reduce the emission of harmful substances. During use, the catalyst can effectively reduce atmospheric pollutants, improve air quality, and comply with the concept of green development. In the preparation process, physical mixing and chemical bonding occur between the components. Through grinding and mixing in a ball mill, the components are evenly dispersed and tightly combined, and then a stable catalytic phase structure is formed through high-temperature sintering.
[0023] In the present invention, the manganese and iron elements in the modified ferromanganese powder have good redox properties and can effectively promote the reduction reaction of nitrogen oxides. The ferromanganese powder provides active sites on the catalyst surface and converts nitrogen oxides into harmless nitrogen and water through redox reactions. Compared with other precious metal catalysts, ferromanganese powder has a lower cost and is suitable for large-scale application.
[0024] The present invention modifies the ferromanganese powder to enhance the activity of the catalyst. The main function of ammonium metavanadate is to provide V2O5. V2O5 has excellent redox ability and catalytic activity. It can effectively promote the reaction of NH3 (ammonia) and NOx The reduction reaction between V2O5 and ferromanganese powder generates harmless N2 and H2O. V2O5 can also produce a synergistic effect with ferromanganese powder and other active components, making it easier for the surface of ferromanganese powder to adsorb and activate nitrogen oxides, thereby accelerating its reduction reaction and improving denitrification efficiency.
[0025] Chromium nitrate is another important additive, which provides Cr 3+ or Cr 6+ Ions have a positive effect on the stability and activity of low-temperature denitration catalysts. The addition of Cr ions can improve the crystal structure of the catalyst, enhance the low-temperature performance and anti-sintering ability of the catalyst. It helps to stabilize the active components of the catalyst and reduce the loss and deactivation of the active components. Chromium nitrate can also form a solid solution or complex with other components in the catalyst, improve the surface acidity and redox properties of the catalyst, which helps the adsorption and activation of NH3 on the catalyst surface and reduce the reaction temperature.
[0026] The addition of ammonium niobium oxalate brings unique sulfur resistance and anti-poisoning ability to this low-temperature denitrification catalyst. As a rare earth metal element, Nb element shows good stability and anti-poisoning performance in the catalyst. Nb2O5 produced by the decomposition of ammonium niobium oxalate at high temperature can effectively inhibit the sintering and deactivation of active components in the catalyst and maintain the long-term activity of the catalyst.
[0027] In addition, the treatment with oxalic acid solution can also remove impurities and unstable phases on the surface of ferromanganese powder, thereby improving its chemical stability and exposing more active sites. The structure formed during the modification process enhances the interaction between ferromanganese powder particles, preventing them from agglomerating or deactivating under high temperature or harsh environment; at the same time, it may also change the surface morphology and pore structure of ferromanganese powder particles by etching or dissolving, thereby improving its specific surface area and adsorption capacity.
[0028] Germanium dioxide is added to the catalyst as a stabilizer to improve the stability of the catalyst at high temperatures. Germanium dioxide can resist the effects of poisoning substances such as sulfur oxides and water vapor in flue gas on the catalyst. Germanium dioxide forms a stable rutile phase structure in the catalyst, which can protect the active components from poisoning and improve sulfur and water resistance. At the same time, it can also participate in surface chemical reactions and promote the conversion of nitrogen oxides.
[0029] Nano-titanium dioxide has a large specific surface area and can provide more active sites. The high specific surface area of nano-titanium dioxide enables the catalyst surface to adsorb more nitrogen oxide molecules. The active sites on its surface can also promote the conversion of nitrogen oxides through redox reactions. In addition, nano-titanium dioxide has excellent adsorption properties and can adsorb and enrich nitrogen oxide molecules, making it easier for them to contact and react with the active sites in the modified ferromanganese powder. The modified ferromanganese powder provides abundant redox active sites. Therefore, there will be a synergistic effect between the two, which can efficiently and low-temperature catalyze the reduction reaction of nitrogen oxides.
[0030] The addition of molybdate can also produce synergistic effects with other components to improve the overall performance of the catalyst; rare earth oxides can be used as carriers or additives for active components in the catalyst due to their unique physical and chemical properties. They have excellent redox properties, thermal stability and good electronic conductivity, and can improve catalytic activity and reduce reaction temperature by optimizing the microstructure and surface properties of the catalyst. At the same time, rare earth oxides can also promote the redox reaction of nitrogen oxides by electron transfer and other means. In the present invention, molybdate and rare earth oxide form a composite phase structure in the catalyst, which jointly improves the catalytic activity and stability of the catalyst, inhibits the sintering and agglomeration of active components in the catalyst, improves the catalyst's ability to resist alkali metals and alkaline earth metals, and maintains the high activity and high selectivity of the catalyst.
[0031] Activated carbon has a very strong adsorption capacity and can adsorb nitrogen oxide molecules and other toxic and harmful substances in flue gas. Activated carbon first adsorbs nitrogen oxide molecules to its surface through physical adsorption, and then converts nitrogen oxides into nitrogen and water through redox reaction under the action of a catalyst.
[0032] The sintering process can promote the formation of a close bond between the components, and improve the mechanical strength and thermal stability of the catalyst. During the sintering process, the shrinkage and rearrangement of the catalyst particles will cause the particle surface to become rougher, thereby increasing the specific surface area. The increase in specific surface area means that the catalyst surface can adsorb more reactant molecules, which is conducive to the catalytic reaction. In the present invention, the modified ferromanganese powder, germanium dioxide, and nano-titanium dioxide are first sintered at 400°C for 4h. During the first sintering process at 400°C, the raw materials such as modified ferromanganese powder, germanium dioxide, and nano-titanium dioxide can form a more stable compound or structure; the addition of molybdate, activated carbon, and rare earth oxides can further promote the uniform distribution of active components, the activation of molecules, and the interaction during the subsequent deionized water dispersion drying and sintering process at 550°C to 650°C, forming an active center that is conducive to the catalytic reaction, thereby improving the catalytic performance.
[0033] Beneficial effects of the present invention:
[0034] The present invention modifies ferromanganese powder to enhance the activity of the catalyst. The modification process changes the surface morphology and pore structure of ferromanganese powder particles, improves its adsorption and catalytic capabilities, and the adjustment of surface chemical properties enables the modified ferromanganese powder to more effectively contact with reactants and generate catalytic reactions.
[0035] The components in the green, high-efficiency, low-temperature denitration catalyst formula prepared by the present invention jointly enhance the denitration performance of the catalyst through synergistic effects. These synergistic effects enable the catalyst to maintain high-efficiency, low-temperature catalytic activity in a complex and changeable flue gas environment, and enhance anti-poisoning ability and stability. DETAILED DESCRIPTION
[0036] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0037] Nano titanium dioxide 50~55%, ferromanganese powder 5~10%, ammonium metavanadate 0.5~1.5%, chromium nitrate 1~2%, ammonium niobium oxalate 1.5~1.8%, germanium dioxide 5~10%, molybdate 2~3%, activated carbon 1~3%, rare earth oxide 2~5%, dispersant 1~2%, binder 2~3%, deionized water 16~18%;
[0038] Formula ratio 1: nano titanium dioxide 50%, ferromanganese powder 6%, ammonium metavanadate 0.5%, chromium nitrate 2%, ammonium niobium oxalate 1.5%, germanium dioxide 10%, ammonium molybdate 2%, activated carbon 3%, lanthanum oxide 5%, polyethylene glycol 2000 2%, polyethylene oxide 20000002%, deionized water 16%;
[0039] Formula ratio 2: nano titanium dioxide 55%, ferromanganese powder 8%, ammonium metavanadate 0.2%, chromium nitrate 1%, ammonium niobium oxalate 1.8%, germanium dioxide 5%, sodium molybdate 3%, activated carbon 2%, cerium oxide 3%, polyethylene glycol 3000 1%, polyethylene oxide 20000003%, deionized water 17%;
[0040] Formula ratio 3: nano titanium dioxide 50%, ferromanganese powder 5%, ammonium metavanadate 1.5%, chromium nitrate 1%, ammonium niobium oxalate 1.5%, germanium dioxide 10%, calcium molybdate 3%, activated carbon 2%, praseodymium oxide 4%, polyethylene glycol 4000 2%, polyethylene oxide 30000002%, deionized water 18%;
[0041] Formula ratio 4: nano titanium dioxide 50%, ferromanganese powder 10%, ammonium metavanadate 1%, chromium nitrate 2%, ammonium niobium oxalate 1.5%, germanium dioxide 8%, magnesium molybdate 2.5%, activated carbon 1%, yttrium oxide 2%, polyethylene glycol 2000 2%, polyethylene oxide 3000000 2%, deionized water 18%.
[0042] Example 1
[0043] S1: Modify the ferromanganese powder. The specific method is as follows:
[0044] S1.1: grinding the ferromanganese powder in a ball mill at a speed of 400 r / min for 4 h to obtain ferromanganese powder with a particle size of 750 mesh;
[0045] S1.2: dissolve ammonium metavanadate, chromium nitrate and ammonium niobium oxalate in 10% by mass oxalic acid solution to obtain a 15% by mass mixed solution, add 1wt% hydrazine hydrate to obtain a mixed solution A, add the ferromanganese powder obtained by grinding in S1.1 to the mixed solution A, heat to 40°C, and perform ultrasonication for 0.5h to obtain a solid-liquid mixture B;
[0046] S1.3: Heat the solid-liquid mixture B to 60°C, stir at 60°C at a speed of 150 r / min for 4 h, cool to room temperature after the reaction is complete, and filter to obtain a mixture C;
[0047] S1.4: The mixture C was dried at 110°C for 14 h under a nitrogen atmosphere to obtain a modified ferromanganese powder;
[0048] S2: According to the formula ratio 1, the modified ferromanganese powder, germanium dioxide and nano titanium dioxide are put into a ball mill for grinding. The speed of the ball mill is 300 r / min. The grinding time is 0.5 h. The ground mixture is heated from room temperature to 400°C in a muffle furnace for 4 h. The heating rate of the muffle furnace is 3°C / min. After sintering, it is cooled to room temperature to obtain a mixture D.
[0049] S3: Put the mixture D, molybdate, activated carbon and rare earth oxide into a high-speed mixer, add deionized water, and then add the dispersant and binder to stir and mix. The speed of the stirring mixer is 4000 r / min. The mixing time is 4 hours to obtain a mixture E. The particle size of the mixture E is 15 mesh.
[0050] S4: The mixture E is extruded into a honeycomb shape by a mold. After completion, it is put into a drying room for drying. It is kept warm in sections at 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃ and 75℃ for 24 hours. Before 45℃, the humidity in the drying room is required to be maintained above 80%. After drying for 300 hours, the moisture content of the finished catalyst is reduced to 20%. After being calcined at 600℃ for 35 hours, a green and efficient low-temperature SCR denitrification catalyst is obtained.
[0051] Example 2
[0052] S1: Modify the ferromanganese powder. The specific method is as follows:
[0053] S1.1: grinding the ferromanganese powder in a ball mill at a speed of 400 r / min for 4 h to obtain ferromanganese powder with a particle size of 750 mesh;
[0054] S1.2: dissolve ammonium metavanadate, chromium nitrate and ammonium niobium oxalate in 10% oxalic acid solution to obtain a 10% mixed solution, add 0.5wt% hydrazine hydrate to obtain a mixed solution A, add the ferromanganese powder obtained by grinding in S1.1 to the mixed solution A, heat to 40°C, and perform ultrasonication for 0.5h to obtain a solid-liquid mixture B;
[0055] S1.3: Heat the solid-liquid mixture B to 60°C, stir at 60°C at a speed of 150 r / min for 4 h, cool to room temperature after the reaction is complete, and filter to obtain a mixture C;
[0056] S1.4: The mixture C was dried at 110°C for 14 h under a nitrogen atmosphere to obtain a modified ferromanganese powder;
[0057] S2: According to the formula ratio 2, the modified ferromanganese powder, germanium dioxide and nano titanium dioxide are put into a ball mill for grinding. The speed of the ball mill is 300 r / min. The grinding time is 0.5 h. The ground mixture is heated from room temperature to 400°C in a muffle furnace for 4 h. The heating rate of the muffle furnace is 3°C / min. After sintering, it is cooled to room temperature to obtain a mixture D.
[0058] S3: Put the mixture D, molybdate, activated carbon and rare earth oxide into a high-speed mixer, add deionized water, and then add the dispersant and binder to stir and mix. The speed of the stirring mixer is 4000 r / min. The mixing time is 5 hours to obtain a mixture E. The particle size of the mixture E is 10 mesh.
[0059] S4: The mixture E is extruded into a honeycomb shape by a mold. After completion, it is put into a drying room for drying. It is kept warm in sections at 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃ and 75℃ for 24 hours. Before 45℃, the humidity in the drying room is required to be maintained above 80%. After drying for 240 hours, the moisture content of the finished catalyst is reduced to 20%. After being calcined at 550℃ for 40 hours, a green and efficient low-temperature SCR denitrification catalyst is obtained.
[0060] Example 3
[0061] S1: Modify the ferromanganese powder. The specific method is as follows:
[0062] S1.1: grinding the ferromanganese powder in a ball mill at a speed of 400 r / min for 4 h to obtain ferromanganese powder with a particle size of 750 mesh;
[0063] S1.2: dissolve ammonium metavanadate, chromium nitrate and ammonium niobium oxalate in 10% by mass oxalic acid solution to obtain a mixed solution with a mass fraction of 20%, and then add 1wt% of hydrazine hydrate to obtain a mixed solution A. Then, put the ferromanganese powder obtained by grinding in S1.1 into the mixed solution A, heat it to 40°C, and perform ultrasonication for 0.5h to obtain a solid-liquid mixture B;
[0064] S1.3: Heat the solid-liquid mixture B to 60°C, stir at 60°C at a speed of 150 r / min for 4 h, cool to room temperature after the reaction is complete, and filter to obtain a mixture C;
[0065] S1.4: The mixture C was dried at 110°C for 14 h under a nitrogen atmosphere to obtain a modified ferromanganese powder;
[0066] S2: According to the formula ratio 3, the modified ferromanganese powder, germanium dioxide and nano titanium dioxide are put into a ball mill for grinding. The speed of the ball mill is 300 r / min. The grinding time is 0.5 h. The ground mixture is heated from room temperature to 400°C in a muffle furnace for 4 h. The heating rate of the muffle furnace is 3°C / min. After sintering, it is cooled to room temperature to obtain a mixture D.
[0067] S3: Put the mixture D, molybdate, activated carbon, and rare earth oxide into a high-speed mixer, add deionized water, and then add the dispersant and binder to stir and mix. The speed of the stirring mixer is 4000 r / min. The mixing time is 5 hours to obtain a mixture E. The particle size of the mixture E is 15 mesh.
[0068] S4: The mixture E is extruded into a honeycomb shape by a mold. After completion, it is put into a drying room for drying. It is kept warm in sections at 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃ and 75℃ for 24 hours. Before 45℃, the humidity in the drying room is required to be maintained above 80%. After drying for 320 hours, the moisture content of the finished catalyst is reduced to 20%. After being calcined at 650℃ for 30 hours, a green and efficient low-temperature SCR denitrification catalyst is obtained.
[0069] Example 4
[0070] S1: Modify the ferromanganese powder. The specific method is as follows:
[0071] S1.1: grinding the ferromanganese powder in a ball mill at a speed of 400 r / min for 4 h to obtain ferromanganese powder with a particle size of 750 mesh;
[0072] S1.2: dissolve ammonium metavanadate, chromium nitrate and ammonium niobium oxalate in 10% by mass oxalic acid solution to obtain a mixed solution with a mass fraction of 20%, and then add 1wt% of hydrazine hydrate to obtain a mixed solution A. Then, put the ferromanganese powder obtained by grinding in S1.1 into the mixed solution A, heat it to 40°C, and perform ultrasonication for 0.5h to obtain a solid-liquid mixture B;
[0073] S1.3: Heat the solid-liquid mixture B to 60°C, stir at 60°C at a speed of 150 r / min for 4 h, cool to room temperature after the reaction is complete, and filter to obtain a mixture C;
[0074] S1.4: The mixture C was dried at 110°C for 14 h under a nitrogen atmosphere to obtain a modified ferromanganese powder;
[0075] S2: According to the formula ratio 4, the modified ferromanganese powder, germanium dioxide and nano titanium dioxide are put into a ball mill for grinding. The speed of the ball mill is 300 r / min. The grinding time is 0.5 h. The ground mixture is heated from room temperature to 400°C in a muffle furnace for 4 h. The heating rate of the muffle furnace is 3°C / min. After sintering, it is cooled to room temperature to obtain a mixture D.
[0076] S3: Put the mixture D, molybdate, activated carbon and rare earth oxide into a high-speed mixer, add deionized water, and then add the dispersant and binder to stir and mix. The speed of the stirring mixer is 4000 r / min. The mixing time is 4 hours to obtain a mixture E. The particle size of the mixture E is 15 mesh.
[0077] S4: The mixture E is extruded into a honeycomb shape by a mold. After completion, it is put into a drying room for drying. It is kept warm in sections at 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃ and 75℃ for 24 hours. Before 45℃, the humidity in the drying room is required to be maintained above 80%. After drying for 240 hours, the moisture content of the finished catalyst is reduced to 20%. It is then calcined at 550℃ for 35 hours to obtain a green and efficient low-temperature SCR denitrification catalyst.
[0078] Comparative Example 1
[0079] In this comparative example, ammonium metavanadate was not added during the modification of ferromanganese powder, and the remaining steps were consistent with those of Example 1.
[0080] Comparative Example 2
[0081] In this comparative example, chromium nitrate was not added during the modification process of ferromanganese powder, and the remaining steps were consistent with those of Example 1.
[0082] Comparative Example 3
[0083] In this comparative example, no ammonium niobium oxalate was added during the modification of the ferromanganese powder, and the remaining steps were consistent with those of Example 1.
[0084] Comparative Example 4
[0085] In this comparative example, the ferromanganese powder is not modified, and the remaining steps are consistent with those in Example 1.
[0086] Comparative Example 5
[0087] In this comparative example, during the catalyst preparation process, the modified ferromanganese powder, germanium dioxide and nano-titanium dioxide were not sintered at 400° C., and the remaining steps were consistent with those in Example 1.
[0088] Comparative Example 6
[0089] In this comparative example, no molybdate was added during the catalyst preparation process, and the remaining steps were consistent with those of Example 1.
[0090] Comparative Example 7
[0091] In this comparative example, no activated carbon was added during the catalyst preparation process, and the remaining steps were consistent with Example 1.
[0092] Comparative Example 8
[0093] In this comparative example, no rare earth oxide is added during the catalyst preparation process, and the remaining steps are consistent with Example 1.
[0094] Comparative Example 9
[0095] In this comparative example, germanium dioxide was not added during the catalyst preparation process, and the remaining steps were consistent with those of Example 1.
[0096] The catalysts prepared in the examples and comparative examples were tested for their denitration performance and their ability to resist poisoning by SO2, H2O, alkali metals, alkaline earth metals, etc., as follows:
[0097] Table 1: Denitrification efficiency at different temperatures
[0098]
[0099] Table 2: Determination of sulfur resistance and water resistance:
[0100]
[0101] Table 3: Alkali metal resistance and alkaline earth metal resistance
[0102]
[0103] It can be seen from the experimental data that the modification of ferromanganese powder in the present invention, the addition of germanium dioxide, nano-titanium dioxide, molybdate, activated carbon, rare earth oxides, and the sintering treatment during the preparation process can effectively improve the denitrification efficiency of the catalyst and improve the resistance to poisoning by SO2, H2O, alkali metals, alkaline earth metals, etc.
[0104] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A green and efficient low-temperature SCR denitration catalyst, characterized in that: The catalyst formula is as follows: by mass percentage, 50-55% nano titanium dioxide, 5-10% ferromanganese powder, 0.5-1.5% ammonium metavanadate, 1-2% chromium nitrate, 1.5-1.8% ammonium niobium oxalate, 5-10% germanium dioxide, 2-3% molybdate, 1-3% activated carbon, 2-5% rare earth oxide, 1-2% dispersant, 2-3% binder, and 16-18% deionized water. The specific process of the preparation method of the green and efficient low-temperature SCR denitration catalyst is as follows: S1: Modify the ferromanganese powder. The specific method is as follows: S1.1: grinding the ferromanganese powder in a ball mill at a speed of 400 r / min for 4 h to obtain ferromanganese powder with a particle size of 750 mesh; S1.2: dissolve ammonium metavanadate, chromium nitrate and ammonium niobium oxalate in 10% oxalic acid solution to obtain a mixed solution with a mass fraction of 10-20%, and then add 0.5-1wt% hydrazine hydrate to obtain a mixed solution A. Then, put the ferromanganese powder obtained by grinding in S1.1 into the mixed solution A, heat it to 40°C, and perform ultrasonication for 0.5h to obtain a solid-liquid mixture B; S1.3: Heat the solid-liquid mixture B to 60°C, stir at 150 r / min for 4 h, cool to room temperature after the reaction is complete, and filter to obtain a mixture C; S1.4: Dry the mixture C at 110° C. for 14 h under a nitrogen atmosphere to obtain a modified ferromanganese powder; S2: Grind the modified ferromanganese powder, germanium dioxide and nano titanium dioxide in a ball mill according to the formula ratio. The speed of the ball mill is 300 r / min. The grinding time is 0.5 h. The ground mixture is heated from room temperature to 400° C. in a muffle furnace and sintered for 4 h. After sintering, it is cooled to room temperature to obtain a mixture D. S3: Place mixture D, molybdate, activated carbon, and rare earth oxide in a high-speed mixer, add deionized water, and then add a dispersant and a binder to stir and mix. The speed of the mixer is 4000 r / min. The mixing time is 4-5 h to obtain a mixture E. S4: The mixture E is extruded into a honeycomb shape by a mold, and then put into a drying room for drying. It is kept warm for 24 hours at 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C and 75°C respectively, wherein the humidity in the drying room is required to be maintained above 80% before 45°C. After drying for at least 240 hours, the moisture content of the finished catalyst product drops below 20%, and then it is calcined at 550~650°C for 30~40 hours to obtain the green and efficient low-temperature SCR denitration catalyst.
2. A green and efficient low-temperature SCR denitration catalyst according to claim 1, characterized in that: The molybdate is one or more of ammonium molybdate, sodium molybdate, calcium molybdate and magnesium molybdate.
3. A green and efficient low-temperature SCR denitration catalyst according to claim 1, characterized in that: The rare earth oxide is one or more of lanthanum oxide, cerium oxide, praseodymium oxide, yttrium oxide, europium oxide, and gadolinium oxide.
4. A green and efficient low-temperature SCR denitration catalyst according to claim 1, characterized in that: The dispersant is polyethylene glycol, and the number average molecular weight of the polyethylene glycol is 2000-4000. The binder is polyethylene oxide, and the number average molecular weight of the polyethylene oxide is 2000000-3000000.
5. A green and efficient low-temperature SCR denitration catalyst according to claim 1, characterized in that: The heating rate of the muffle furnace in S2 is 3°C / min.
6. A green and efficient low-temperature SCR denitration catalyst according to claim 1, characterized in that: The particle size of the mixture E obtained in S3 is 10-15 meshes.
Citation Information
Patent Citations
Catalyst for synergistic control of nitrate and mercury and preparation method thereof
CN105263617B
Low-temperature denitration catalyst and preparation method therefor
CN110743561A
Non-metal auxiliary ultralow-temperature water-resistant SCR catalyst and preparation method thereof
CN117123240A